“You Win, You Buy”—How Continuous Win Effect Influence Consumers' Price Perception: An ERP Study - Ma, Qingguo; Zhang, Linanzi; Wang, Manlin (Frontiers in Neuroscience, 2018)
Price played an important role in most purchases. Buying behavior was strongly determined by consumers’ price expectations. Emotion as a research hotspot was demonstrated to be ubiquitous in marketing and influenced purchase processing as well. This study addressed interests upon whether emotion arousal would influence consumers’ price perceptions and their willingness to purchase. Compared to such emotion researches which normally adopted emotional pictures as priming stimuli, we creatively employed a two-player “Finger Play” (FP) game without monetary gains or losses to arouse subjects’ emotion in the experiment. A 2 (FP Game Results: Continuous Win versus Continuous Lose) by 2 (Price Conditions: High Price versus Low Price) Event-Related Potentials (ERPs) experiment was designed to investigate whether game results would arouse different emotions and influence subjects’ perception of product price. Both behavioral and ERP results indicated that subjects’ price perception was deeply impacted by emotions induced from continuous win/lose experiences.